Local democracy in Indian and South African cities: A comparative literature review - Benit Gbaffou, Claire (Wits University Press, Johannesburg, 2011)
The local level has become since the 1990s an important arena of development of democracy in most countries of the world – in a move sometimes described as part of “the third wave of democratization” (Huntington 1992), encouraged both by progressive movements seeking a form of grassroots democracy, and by the World Bank as a new form of governance. India and South Africa are no exception, and both countries have implemented reforms of local government in the mid 1990s, with the objective of broadening and deepening democracy. This chapter aims at comparing the political and academic debates that took place in South Africa and India concerning decentralization, and more broadly local democracy, in an urban context1. We believe, with Hantrais, that “the definition and understanding of concepts and the relationship between concepts and contexts are of critical concern in comparative research that crosses national, societal, cultural and linguistic boundaries” (Hantrais 2009: 72). Through a literature review and a contextualization of local democracy’s history, institutions, and practices, this joint chapter aims at identifying the commonalities and differences in the political and social stakes contained in the debates on “local democracy”.
Keywords: Local democracy. Indian and South African cities. Development of democracy.